Insulin resistance is associated with reductions in specific cognitive domains and increases in CSF tau in cognitively normal adults - Laws, S.; Gaskin, S.; Woodfield, A.; Srikanth, V.; Bruce, D.; Fraser, P.; Porter, T.; Newsholme, Philip; Wijesekara, N.; Burnham, S.; Doré, V.; Li, Q.; et al. (Nature Publishing Group, 2017)
Growing evidence supports the hypothesis that type 2 diabetes (T2D) increases the risk of developing dementia. Experimental evidence from mouse models demonstrates that the induction of T2D/insulin resistance (IR) can promote the accumulation of Alzheimer's disease (AD) pathological features. However, the association of T2D with pathological and clinical phenotypes in humans is unclear. Here we investigate the relationship of indices of IR (HOMA-IR) and pancreatic ß-cell function (HOMA-B) with cognitive performance across several domains (Verbal/Visual Episodic Memory, Executive Function, Language and a measure of Global cognition) and AD biomarkers (CSF Aß42, T-tau/P-tau, hippocampal volume and neocortical Aß-amyloid burden). We reveal that HOMA-IR (p < 0.001) incrementally increases across diagnostic groups, becoming significantly elevated in the AD group compared with cognitively normal (CN) adults. In CN adults, higher HOMA-IR was associated with poorer performance on measures of verbal episodic memory (p = 0.010), executive function (p = 0.046) and global cognition (p = 0.007), as well as with higher CSF T-tau (p = 0.008) and P-tau (p = 0.014) levels. No association was observed with CSF Aß or imaging modalities. Together our data suggest that IR may contribute to reduced cognitive performance and the accumulation of CSF tau biomarkers in cognitively normal adults.